Advances in Glomeromycota taxonomy and classification - Oehl, Fritz (Nationaal Herbarium Nederland & Centraallbureau voor Schimmelcultures, 2011)
Concomitant morphological and molecular analyses have led to major breakthroughs in the taxonomic organization of the phylum Glomeromycota. Fungi in this phylum are known to form arbuscular mycorrhiza, and so far three classes, five orders, 14 families and 29 genera have been described. Sensu lato, spore formation in 10 of the arbuscular mycorrhiza-forming genera is exclusively glomoid, one is gigasporoid, seven are scutellosporoid, four are entrophosporoid, two are acaulosporoid, and one is pacisporoid. Spore bimorphism is found in three genera, and one genus is associated with cyanobacteria. Here we present the current classification developed in several recent publications and provide a summary to facilitate the identification of taxa from genus to class level.